The ties that bind: Trade and foreign policy between China and Latin America (2016)
China’s international political success and its growing ties with Latin America have coincided with the deterioration of the relations between Unites States and Latin America. Even if this fact has been explained by some authors as a consequence of China’s foreign policy, we show that Latin America’s foreign policy has been formulated independently, and that the bad moment in the relations between United States and Latin America cannot be translated as an alignment with China’s interests. © 2016, Universidad Nacional de Colombia. All rights reserved.